BISNIS KALIGRAFI DALAM TINJAUAN EKONOMI ISLAM DI RUMAH KALIGRAFI AN-NIDA MEDAN-SUMATERA UTARA - Almita Wiguna; Sartika Alpianti Manurung; Devi Puspita Ardani (Jurnal Ekshis, 2024)
The art of Islamic calligraphy is a work of art that has its own characteristics of beauty so that it has a high selling value. At this time, many institutions or special places were deliberately built to foster one's talent for the art of calligraphy as well as to become sales centers for calligraphy tools or even the works of calligraphy itself, one of which is the An-Nida Calligraphy House. This study aims to find out how the calligraphy business is developing according to economics at the An-Nida Calligraphy House from its inception to today. the method used in this study is a qualitative method, through literature review and interviews as data collection techniques, and descriptive statistics are data analysis techniques used. The results of this study indicate that the development of the calligraphy business at the Calligraphy House which was built in 2017 has increased every year, and the various types of goods traded are increasingly diverse. This is evidenced by the increase in consumers and the progress of the construction of the Calligraphy House from year to year.